Optoelectrical Properties of NiInZnO (NIZO) Thin Films (Journal of Solar Energy Research Updates, 2019)
This report presents the fabrication and characterization of x % Ni - InZnO (NIZO) Schottky diodes. The structural, optical and electrical properties of the fabricate Al/p-Si / x % Ni - InZnO /Au photodiodes were investigated. An average visible transmittance of about 75% - 85% has been obtained in the visible-light to near-infrared wavelength region. The optical bandgap was 3.17 ± 0.02 eV. Current-Voltage measurements were conducted to analyze the photodiode behavior under dark and light illumination. The reverse bias current increases together with increasing light illumination. The observed I-V results confirm the photoconductive and photovoltaic properties of the fabricated diode. There is an exponential relationship between the current and the voltage in the forward bias, confirming the rectification performance of the photodiode. The electrical properties of the fabricated photodiodes were evaluated using Cheung- Cheung and Norde’s methods. The transient photocurrent, capacitance-voltage-frequency and conductance-voltagefrequency plots indicate that the diode is very sensitive to light illumination. We also observe a strong correlation between capacitance and conductance on frequency, this was explained based on the presence of interface states. The obtained results suggest that the Ni-doped InZnO photodiodes can be useful in photovoltaic and optoelectronic applications.